A Ti nanotube, preparation method and use thereof

By depositing metal Ti on the surface of carbon nanorods and removing carbon nanorods to prepare Ti nanotubes, the problem of difficulty in controlling uniformity and length of Ti nanotubes in the prior art is solved, and higher uniformity and controllable length are achieved, which is suitable for industrial production.

CN110877891BActive Publication Date: 2025-03-25SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201911285324.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-12-13
Publication Date
2025-03-25
Estimated Expiration
2039-12-13

AI Technical Summary

Technical Problem

In the prior art, the synthesis of Ti nanotubes adopts chemical vapor deposition method, resulting in poor uniformity of the tube, with an upper limit of 5 to 10 μm, and the preparation method is complicated, making it not suitable for industrial production.

Method used

By depositing metal Ti on the surface of the carbon nanorod, Ti carbon nanorods were obtained, and Ti nanotubes were obtained by removing the carbon nanorods. This method can control the thickness of the Ti layer to ensure the uniformity and controllable length of the Ti nanotube.

Benefits of technology

A significant improvement in uniformity and length of Ti nanotubes has been achieved, simplified the preparation process, made it suitable for industrial production, and broadened its potential use in biomedical and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110877891B_ABST
    Figure CN110877891B_ABST
Patent Text Reader

Abstract

The present invention relates to a Ti nanotube, a preparation method and use thereof. The preparation method of the Ti nanotube comprises the following steps: (1) depositing metal Ti on the surface of a carbon nanorod to obtain a Ti-plated carbon nanorod; (2) removing the carbon nanorods in the Ti-plated carbon nanorod to obtain a Ti nanotube. The preparation method of the present invention can well control the thickness of the deposited metal Ti, and the obtained Ti nanotube has good uniformity; at the same time, compared with the Ti nanotube prepared by the chemical vapor deposition method in the prior art, the length of the Ti nanotube obtained by the method of the present invention is controllable, the same as the length of the carbon nanorod, and far exceeds the length of the Ti nanotube prepared by the chemical vapor deposition method while ensuring the tubular structure. The preparation method of the present invention is simple, can be industrialized, and has excellent practical prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of micro-nano processing, and in particular relates to a Ti nanotube, a preparation method and application thereof. Background Art

[0002] Nanotechnology emerged in the late 1980s and has great theoretical and application value. Nanomaterials are called "the most promising materials of the 21st century". Nanomaterials usually refer to materials with at least one dimension in the nanoscale range in three-dimensional space or are composed of nanoscale materials as basic units and have physical and chemical properties different from conventional materials.

[0003] Studies have shown that Ti metal has good biocompatibility and has great development potential in my country's biomedical materials and medical device industries. Single Ti nanotubes (TNTs) have strong transmembrane capabilities and can be combined with biological molecules and small drug molecules with poor water solubility and low bioavailability, and can be used as gene transporters, targeted drug delivery, etc.

[0004] In the prior art, the synthesis of Ti nanotubes is mostly prepared by chemical vapor deposition. The upper limit of the length of Ti nanotubes prepared by chemical vapor deposition is between 5 and 10 μm, otherwise there will be adhesion between the tubes. At the same time, there are many boundary conditions that affect the uniformity of the chemical vapor deposition coating, mainly including gas distribution, vacuum degree, numerical temperature, etc., and the uniformity of the obtained Ti nanotubes is poor.

[0005] Therefore, there is a need in the art to develop a novel method for preparing Ti nanotubes, wherein the Ti nanotubes obtained by the method have good uniformity, and the preparation method is simple and can be industrially produced. Summary of the invention

[0006] In view of the shortcomings of the prior art in preparing Ti nanotubes by chemical vapor deposition, the present invention aims to provide a Ti nanotube, a preparation method and use thereof. The Ti nanotubes obtained by the method of the present invention have good uniformity, controllable length of the Ti nanotubes, and a simple preparation method, which can be industrialized.

[0007] In order to solve the above problems, the present invention adopts the following technical solutions:

[0008] One of the purposes of the present invention is to provide a method for preparing Ti nanotubes, the method comprising the following steps:

[0009] (1) depositing metal Ti on the surface of carbon nanorods to obtain Ti-coated carbon nanorods;

[0010] (2) removing the carbon nanorods from the Ti-coated carbon nanorods to obtain Ti nanotubes.

[0011] The preparation method of the present invention can well control the thickness of the deposited metal Ti, and the obtained Ti nanotubes have good uniformity; at the same time, compared with the Ti nanotubes prepared by the chemical vapor deposition method in the prior art, the length of the Ti nanotubes obtained by the method of the present invention is controllable, the same as the length of the carbon nanorods, and far exceeds the length of the Ti nanotubes prepared by the chemical vapor deposition method while ensuring the tubular structure. The preparation method of the present invention is simple, can be industrialized, and has excellent practical prospects.

[0012] Preferably, the preparation method of depositing metal Ti on the surface of carbon nanorods in step (1) comprises:

[0013] (a) placing the first substrate carrying the carbon nanorods into an electron beam evaporation system to deposit metal Ti on the upper surface of the carbon nanorods;

[0014] (b) transferring the carbon nanorods with metal Ti deposited on the upper surface obtained in step (a) to a second substrate, and depositing metal Ti on the lower surface.

[0015] The present invention uses an electron beam evaporation system to deposit metal Ti, which can control the unevenness of the joints of the two-sided coatings (the upper surface and the lower surface of the carbon nanorods) to be between 20% and 30%, and the equipment coating rate is stable.

[0016] The upper surface of the carbon nanorod described in the present invention is: in the carbon nanorod, the surface above the maximum cross-section parallel to the first substrate (the surface away from the first substrate) is the upper surface of the carbon nanorod, and the surface below the maximum cross-section parallel to the first substrate (in contact with the first substrate) is the lower surface of the carbon nanorod.

[0017] Preferably, the thickness of the metal Ti deposited on the surface of the carbon nanorods in step (1) is 10 to 100 nm, for example, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm or 90 nm.

[0018] The thickness of the deposited metal Ti is selected to be 10-100 nm. If the thickness of the deposited metal Ti is too large, the specific surface area and lightweight application efficiency will be reduced; if the thickness of the deposited metal Ti is too small, the mechanical properties will be reduced.

[0019] Preferably, in the process of depositing metal Ti on the surface of carbon nanorods in step (1), the vacuum degree of the reaction system is 10 -6 ~5×10 -6 Torr, for example, 1.5×10 -6 Torr, 2×10 -6 Torr, 2.5×10 -6 Torr, 3×10 -6 Torr, 3.5×10 -6Torr, 4×10 -6 Torr or 4.5×10 -6 Torr et al.

[0020] Preferably, the preparation process of the first substrate carrying carbon nanorods comprises:

[0021] (a1) preparing a carbon nanorod dispersion;

[0022] (a2) placing a first substrate in a container, adding a first solvent so that the liquid level of the first solvent is higher than the first substrate, and then adding a second solvent, so that stratification occurs between the first solvent and the second solvent;

[0023] (a3) adding the carbon nanorod dispersion to the layered liquid surface between the first solvent and the second solvent;

[0024] (a4) Pulling the first substrate out of the container to obtain the first substrate carrying carbon nanorods.

[0025] In step (a2) of the present invention, a small clean glass spacer can be placed under the first substrate, so that the first substrate is stacked on the small glass spacer to facilitate the subsequent pulling out of the first substrate. The present invention does not specifically limit the height of the second solvent added in step (a2), as long as there is a clear stratification between the first solvent and the second solvent. Those skilled in the art can make a selection according to actual conditions. The exemplary height of the second solvent selected in the present invention is 3 to 8 mm.

[0026] Preferably, the concentration of the carbon nanorod dispersion in step (a1) is 1 to 3 mg / mL, for example, 1.2 mg / mL, 1.5 mg / mL, 1.8 mg / mL, 2 mg / mL, 2.2 mg / mL, 2.5 mg / mL or 2.8 mg / mL.

[0027] The concentration of the carbon nanorod dispersion of the present invention is 1-3 mg / mL. If the concentration is too high, the sample will be too dense, which is not conducive to the deposition uniformity of a single carbon nanorod; if the concentration is too low, the preparation efficiency will be reduced.

[0028] Preferably, the diameter of the carbon nanorods in the carbon nanorod dispersion in step (a1) is 100nm~10μm (for example, 200nm, 300nm, 400nm, 500nm, 600nm, 800nm, 900nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm or 9μm, etc.), and the length of the carbon nanorods is preferably 0.5~100μm (for example, 1μm, 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm or 90μm, etc.).

[0029] Preferably, the solvent in the carbon nanorod dispersion in step (a1) comprises any one of ethanol, methanol, ethanol and isopropanol, or a combination of at least two of them.

[0030] Preferably, in step (a2), the first substrate comprises a silicon wafer or a glass wafer.

[0031] Preferably, before step (a2), the method further includes immersing the first substrate in a piranha solution, and then washing and drying the substrate.

[0032] The present invention immerses the first substrate in a piranha solution, then washes it with deionized water and blows it dry with high-purity nitrogen gas to preserve intact hydroxyl groups on the surface and improve surface wettability.

[0033] Preferably, the cleaning is performed using deionized water.

[0034] Preferably, the drying is carried out by blowing with nitrogen.

[0035] Preferably, in step (a2), the first solvent is water, preferably deionized water.

[0036] Preferably, in step (a2), the second solvent is any one of n-hexane, benzene, toluene, xylene, chlorobenzene, dichlorobenzene and dichloromethane, or a combination of at least two thereof.

[0037] Preferably, after step (a4), a drying process is also included, preferably drying at 60-80°C (e.g., 62°C, 65°C, 68°C, 70°C, 72°C, 75°C or 78°C, etc.) for 1-3h (e.g., 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h or 2.8h, etc.).

[0038] Preferably, the rate of metal Ti deposition in step (a) is Preferably For example or wait.

[0039] Preferably, after step (a), the method further comprises subjecting the product obtained in step (a) to silanization treatment.

[0040] Preferably, the silanization treatment is: adding TMCS (trimethylchlorosilane) dropwise onto the surface of the product obtained in step (a).

[0041] Preferably, the silanization treatment time is 10 to 20 min, for example, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min or 19 min.

[0042] Preferably, the preparation process of the second substrate in step (b) includes: coating a mixed material of PDMS (polydimethylsiloxane) and sylgard 184 on a substrate, and baking to obtain a second substrate.

[0043] Preferably, the substrate comprises a silicon wafer or a glass wafer.

[0044] Preferably, the coating method is spin coating.

[0045] Preferably, the rotation speed of the spin coating is 500-1500 rpm, for example, 600 rpm, 700 rpm, 800 rpm, 900 rpm, 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm or 1400 rpm.

[0046] Preferably, the spin coating time is 30 to 90 s, such as 40 s, 50 s, 60 s, 70 s or 80 s.

[0047] Preferably, the mixed material is coated to a thickness of 0.4-0.8 mm, such as 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm or 0.8 mm.

[0048] Preferably, in the mixed material, the mass ratio of PDMS to sylgard 184 is (8-15):1, for example, 9:1, 10:1, 11:1, 12:1, 13:1 or 14:1, etc.

[0049] Preferably, the baking temperature is 60-90°C, for example, 65°C, 70°C, 75°C, 80°C or 85°C.

[0050] Preferably, the baking time is 5 to 15 min, for example, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min or 14 min.

[0051] Preferably, the process of transferring the carbon nanorods with metal Ti deposited on the upper surface to the second substrate in step (b) includes: laminating the side of the second substrate coated with the mixed material with the side of the carbon nanorods with metal Ti deposited on them, baking at 60-90°C (for example, 65°C, 70°C, 75°C, 80°C or 85°C, etc.) for 5-15min (for example, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min or 14min, etc.), and peeling off the first substrate.

[0052] In the process of laminating the side of the second substrate coated with the mixed material with the side of the carbon nanorod deposited with metal Ti, the first substrate and the second substrate are placed in parallel.

[0053] Preferably, the thickness of the metal Ti deposited on the upper surface of the carbon nanorods in step (a) is the same as the thickness of the metal Ti deposited on the lower surface of the carbon nanorods in step (b).

[0054] Preferably, after step (b), the process further includes peeling off the second substrate, washing with an alkaline solution, washing with deionized water and drying.

[0055] Preferably, the alkaline solution washing is ultrasonic washing in a NaOH solution, preferably ultrasonically washing in a 0.1-1 mol / L (e.g., 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.8 mol / L or 0.9 mol / L, etc.) NaOH solution for 4-8 min (e.g., 4.5 min, 5 min, 5.5 min, 6 min, 6.5 min, 7 min or 7.5 min, etc.).

[0056] Preferably, the process of removing the carbon nanorods from the Ti-coated carbon nanorods in step (2) comprises: burning the Ti-coated carbon nanorods in oxygen.

[0057] Preferably, the burning temperature is 300-700°C, for example, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C.

[0058] Since the amount of samples processed in each batch is uncertain, the present invention does not specifically limit the burning time. The time until all carbon nanorods are burned out by detecting the tail gas is the burning time.

[0059] Preferably, after the burning, a reducing agent is added to carry out a reduction process.

[0060] Preferably, the reducing agent comprises Mg powder and / or zinc powder.

[0061] Preferably, the mass ratio of the reducing agent added to the Ti-plated carbon nanotubes is (0.5-1.5):1, for example, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1 or 1.4:1, etc.

[0062] Preferably, the atmosphere of the reduction process is a nitrogen atmosphere.

[0063] Preferably, the temperature of the reduction process is 600-700°C, for example, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C or 690°C.

[0064] Preferably, the reduction process lasts for 5 to 10 hours, such as 6 hours, 7 hours, 8 hours or 9 hours.

[0065] Preferably, after adding the reducing agent, the process further includes pickling, water washing and drying. Preferably, the pickling is ultrasonically carried out in an acid solution for 5 to 15 minutes, for example, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes or 14 minutes.

[0066] Preferably, the acid solution is any one of hydrochloric acid solution, sulfuric acid solution, phosphoric acid solution, oxalic acid solution and acetic acid solution, or a combination of at least two thereof.

[0067] Preferably, the concentration of the hydrochloric acid solution is less than 7wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or 6wt%, etc.

[0068] Preferably, the concentration of the sulfuric acid solution is <5wt%, for example 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt% or 4.5wt%, etc.

[0069] Preferably, the concentration of the phosphoric acid solution is less than 85wt%, for example 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%, etc.

[0070] Preferably, the concentration of the oxalic acid solution is less than 85wt%, for example 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%, etc.

[0071] Preferably, the concentration of the acetic acid solution is less than 85wt%, for example 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt% or 80wt%, etc.

[0072] The concentrations of the hydrochloric acid solution, sulfuric acid solution, phosphoric acid solution, oxalic acid solution and acetic acid solution described in the present invention are their concentrations at room temperature.

[0073] As a preferred technical solution, a method for preparing Ti nanotubes according to the present invention comprises the following steps:

[0074] (1) Pretreatment of carbon nanorods:

[0075] (a) The glass and silicon wafers were immersed in piranha solution, then rinsed with deionized water and dried with nitrogen gas;

[0076] (b) dispersing the carbon nanorods in an ethanol solution and ultrasonicating for 5 to 15 minutes to prepare a carbon nanorod dispersion with a concentration of 1 to 3 mg / mL;

[0077] (c) Take a clean small culture dish, put a clean small glass spacer and a silicon wafer in order, and stack the silicon wafer on the small glass spacer;

[0078] (d) adding deionized water until the liquid level is higher than the upper surface of the silicon wafer, and then adding n-hexane to cause stratification;

[0079] (e) using a pipette to drop the carbon nanorod dispersion from the edge of the culture dish so that it spreads into a monolayer film at the layering surface of n-hexane and water;

[0080] (f) Using tweezers, carefully and slowly reach under the liquid surface, pick up the silicon wafer, slowly pull out the silicon wafer, and dry it in a drying oven at 60-80° C. for 1-3 h to obtain a silicon wafer loaded with carbon nanorods;

[0081] (2) Preparation of Ti-coated carbon nanorods:

[0082] (g) placing the silicon wafer loaded with carbon nanorods into an electron beam evaporation system, and making the vacuum degree in the evaporation chamber reach 10 -6 ~5×10 -6 Torr, at the upper surface of the carbon nanorod at a rate Depositing metal Ti with a thickness of 10 to 100 nm;

[0083] (h) adding a few drops of TMCS to the product obtained in step (g) in a culture dish, and silanizing the sample for 10 to 20 minutes;

[0084] (i) Spin-coat a 0.4-0.8 mm thick mixed material of PDMS and sylgard 184 in the ratio of (8-15):1 on a clean silicon wafer, and bake at a low temperature of 60-90° C. for 5-15 min;

[0085] (j) laminating the silicon wafer coated with the mixed material on the mixed material surface with the surface of the carbon nanorods in the sample obtained in step (h) on which the metal Ti is deposited, baking at 60 to 90° C. for 5 to 15 min, and peeling off the silicon wafer;

[0086] (k) repeating step (g) with the sample obtained in step (j) to deposit the same thickness of metal Ti on the lower surface of the carbon nanorods;

[0087] (l) peeling off the silicon wafer coated with the mixed material, ultrasonicating in a 0.1-1 mol / L NaOH solution for 4-8 min, centrifuging and filtering out the precipitate, washing with deionized water and drying;

[0088] (3) Preparation of Ti nanotubes:

[0089] (m) taking the sample in step (l) and burning it in oxygen at 300-700° C., and cooling it;

[0090] (n) then adding Mg powder, treating at 600-700°C for 5-10 hours in nitrogen, and cooling to room temperature;

[0091] (o) The sample is taken out and added into a dilute hydrochloric acid solution, ultrasonicated for 5 to 15 minutes, washed with deionized water and dried to obtain Ti nanotubes.

[0092] Figure 1 Schematic diagram of depositing metal Ti on the upper surface of carbon nanorods according to the present invention, wherein 1 is a first substrate, 2 is a carbon nanorod, and 3 is metal Ti; Figure 2 Schematic diagram of depositing metal Ti on the lower surface of carbon nanorods in the present invention, in which 4 is the second substrate, 2 is the carbon nanorods, and 3 is the metal Ti; as can be seen from the figure, when the carbon nanorods are transferred to the second substrate, the metal Ti deposited on the upper surface is in complete contact with the second substrate, and then when the metal Ti is deposited on the lower surface, the problem of no deposition or excessive deposition in some areas can be effectively avoided. Figure 3 It is a schematic diagram of the structure of the Ti nanotube obtained by the present invention.

[0093] The second object of the present invention is to provide a Ti nanotube, which is prepared by the method described in one of the objects.

[0094] Preferably, the sidewall thickness of the Ti nanotube is 10-100 nm, for example, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm or 90 nm.

[0095] Preferably, the length of the Ti nanotube is 0.5-100 μm, for example, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm or 90 μm.

[0096] Preferably, the inner diameter of the Ti nanotube is 100 nm to 10 μm, for example, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 800 nm, 900 nm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm or 9 μm.

[0097] The third object of the present invention is to provide a use of the Ti nanotubes as described in the second object, wherein the Ti nanotubes are used in the field of life sciences, preferably any one or a combination of at least two of biotechnology injection equipment, biosensors, nanocapsules, scaffolds, tissue engineering and drug delivery.

[0098] Compared with the prior art, the present invention has the following beneficial effects:

[0099] The method of the present invention can well control the thickness of the deposited metal Ti, and the obtained Ti nanotubes have good uniformity; at the same time, compared with the Ti nanotubes prepared by the chemical vapor deposition method in the prior art, the length of the Ti nanotubes obtained by the method of the present invention is controllable, the same as the length of the carbon nanorods, and far exceeds the length of the Ti nanotubes prepared by the chemical vapor deposition method while ensuring the tubular structure. The preparation method of the present invention is simple, can be industrialized, and has excellent practical prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0100] Figure 1 Schematic diagram of depositing metal Ti on the upper surface of carbon nanorods provided by the present invention, in which 1 is a first substrate, 2 is a carbon nanorod, and 3 is metal Ti;

[0101] Figure 2 Schematic diagram of depositing metal Ti on the lower surface of carbon nanorods provided by the present invention, in which 4 is a second substrate, 2 is a carbon nanorod, and 3 is metal Ti;

[0102] Figure 3 It is a schematic diagram of the structure of the Ti nanotube provided by the present invention. DETAILED DESCRIPTION

[0103] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0104] Example 1

[0105] (1) Pretreatment of carbon nanorods:

[0106] (a) The glass and silicon wafers were immersed in piranha solution, then rinsed with deionized water and dried with nitrogen gas;

[0107] (b) dispersing carbon nanorods with a diameter of 2 μm and a length of 50 μm in an ethanol solution and ultrasonicating for 10 min to prepare a carbon nanorod dispersion with a concentration of 2 mg / mL;

[0108] (c) Take a clean small culture dish, put a clean small glass spacer and a silicon wafer in order, and stack the silicon wafer on the small glass spacer;

[0109] (d) adding deionized water until the liquid level is higher than the upper surface of the silicon wafer, and then adding n-hexane to cause stratification;

[0110] (e) using a pipette to drop the carbon nanorod dispersion from the edge of the culture dish so that it spreads into a monolayer film at the layering surface of n-hexane and water;

[0111] (f) Using tweezers, carefully and slowly reach under the liquid surface, pick up the silicon wafer, slowly pull it out, and dry it in a drying oven at 70°C for 2 h to obtain a silicon wafer loaded with carbon nanorods;

[0112] (2) Preparation of Ti-coated carbon nanorods:

[0113] (g) placing the silicon wafer loaded with carbon nanorods into an electron beam evaporation system, and making the vacuum degree in the evaporation chamber reach 10 - 6 Torr, at the upper surface of the carbon nanorod at a rate Depositing metal Ti with a thickness of 50 nm;

[0114] (h) adding 1 mL of TMCS to the product obtained in step (g) in a culture dish, and silanizing the sample for 15 min;

[0115] (i) Spin coating a 0.5 mm thick layer of a clean silicon wafer with a mixture of PDMS and sylgard 184 in a ratio of 10:1 at a spin coating speed of 1000 rpm for 60 s and baking at 80° C. for 10 min;

[0116] (j) laminating the side of the silicon wafer coated with the mixed material containing the mixed material with the side of the carbon nanorods in the sample obtained in step (h) on which the metal Ti is deposited, baking at 80° C. for 5 min, and peeling off the silicon wafer;

[0117] (k) repeating step (g) with the sample obtained in step (j) to deposit metal Ti of the same thickness (50 nm) on the lower surface of the carbon nanorods;

[0118] (l) peeling off the silicon wafer coated with the mixed material, ultrasonicating in a 0.5 mol / L NaOH solution for 5 min, centrifuging and filtering out the precipitate, washing with deionized water and drying;

[0119] (3) Preparation of Ti nanotubes:

[0120] (m) taking the sample in step (l) and burning it in oxygen at a temperature of 300° C. until all the carbon nanorods are removed, and cooling;

[0121] (n) Mg powder was then added, the mixture was treated at 650 °C for 7 h in nitrogen, and then cooled to room temperature in a nitrogen environment;

[0122] (o) The sample was taken out and added with a 5 wt % dilute hydrochloric acid solution, ultrasonicated for 10 min, washed with deionized water and dried to obtain Ti nanotubes with an inner diameter of 2 μm, a length of 50 μm and a side wall thickness of 50 nm.

[0123] Example 2

[0124] The difference from Example 1 is that the deposition thickness of metal Ti in step (g) and step (k) is both 10 nm.

[0125] Example 3

[0126] The difference from Example 1 is that the deposition thickness of metal Ti in step (g) and step (k) is both 100 nm.

[0127] Example 4

[0128] (1) Pretreatment of carbon nanorods:

[0129] (a) The glass and silicon wafers were immersed in piranha solution, then rinsed with deionized water and dried with nitrogen gas;

[0130] (b) dispersing carbon nanorods with a diameter of 4 μm and a length of 80 μm in an ethanol solution and ultrasonicating for 15 min to prepare a carbon nanorod dispersion with a concentration of 3 mg / mL;

[0131] (c) Take a clean small culture dish, put a clean small glass spacer and a silicon wafer in order, and stack the silicon wafer on the small glass spacer;

[0132] (d) adding deionized water until the liquid level is higher than the upper surface of the silicon wafer, and then adding n-hexane to cause stratification;

[0133] (e) using a pipette to drop the carbon nanorod dispersion from the edge of the culture dish so that it spreads into a monolayer film at the layering surface of n-hexane and water;

[0134] (f) Using tweezers, carefully and slowly reach under the liquid surface, pick up the silicon wafer, slowly pull it out, and dry it in a drying oven at 80°C for 1 h to obtain a silicon wafer loaded with carbon nanorods;

[0135] (2) Preparation of Ti-coated carbon nanorods:

[0136] (g) placing the silicon wafer loaded with carbon nanorods into an electron beam evaporation system, and making the vacuum degree in the evaporation chamber reach 5×10 -6 Torr, at the upper surface of the carbon nanorod at a rate Depositing metal Ti with a thickness of 80 nm;

[0137] (h) adding 2 mL of TMCS to the product obtained in step (g) in a culture dish, and silanizing the sample for 20 min;

[0138] (i) Spin coating a 0.7 mm thick layer of a mixed material of PDMS and sylgard 184 in a ratio of 12:1 on a clean silicon wafer at a speed of 1300 rpm for 80 s and baking at 90° C. for 8 min;

[0139] (j) laminating the side of the silicon wafer coated with the mixed material containing the mixed material with the side of the carbon nanorods in the sample obtained in step (h) on which the metal Ti is deposited, baking at 90° C. for 5 min, and peeling off the silicon wafer;

[0140] (k) repeating step (g) with the sample obtained in step (j) to deposit metal Ti of the same thickness (80 nm) on the lower surface of the carbon nanorods;

[0141] (l) peeling off the silicon wafer coated with the mixed material, ultrasonicating in a 0.7 mol / L NaOH solution for 8 min, centrifuging and filtering out the precipitate, washing with deionized water and drying;

[0142] (3) Preparation of Ti nanotubes:

[0143] (m) taking the sample in step (l) and burning it in oxygen at a temperature of 700° C. until all the carbon nanorods are removed, and cooling;

[0144] (n) then adding zinc powder, treating at 700°C for 5 h in nitrogen, and cooling to room temperature;

[0145] (o) The sample was taken out and added with 35 wt % acetic acid solution, ultrasonicated for 8 min, washed with deionized water and dried to obtain Ti nanotubes with an inner diameter of 4 μm, a length of 80 μm and a side wall thickness of 80 nm.

[0146] The Ti nanotubes prepared in Examples 1-4 of the present invention have good uniformity and controllable length, and have excellent practical prospects.

[0147] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing Ti nanotubes, characterized in that: The method comprises the following steps: (1) depositing metal Ti on the surface of carbon nanorods to obtain Ti-coated carbon nanorods; The preparation method of depositing metal Ti on the surface of carbon nanorods comprises: (a) placing the first substrate carrying the carbon nanorods into an electron beam evaporation system to deposit metal Ti on the upper surface of the carbon nanorods; (b) transferring the carbon nanorods with metal Ti deposited on the upper surface obtained in step (a) to a second substrate, and depositing metal Ti on the lower surface; (2) removing the carbon nanorods from the Ti-coated carbon nanorods to obtain Ti nanotubes; The process of removing the carbon nanorods from the Ti-plated carbon nanorods comprises: The Ti-plated carbon nanorods are burned in oxygen; after the burning, a reducing agent is added to carry out a reduction process; after the adding of the reducing agent, pickling, water washing and drying processes are also carried out.

2. The method according to claim 1, characterized in that The thickness of the metal Ti deposited on the surface of the carbon nanorods in step (1) is 10 to 100 nm.

3. The method according to claim 1, characterized in that In the process of depositing metal Ti on the surface of carbon nanorods in step (1), the vacuum degree of the reaction system is 10 -6 ~5×10 -6 Torr.

4. The method according to claim 1, characterized in that The preparation process of the first substrate carrying carbon nanorods comprises: (a1) preparing a carbon nanorod dispersion; (a2) placing a first substrate in a container, adding a first solvent so that the liquid level of the first solvent is higher than the first substrate, and then adding a second solvent, so that a layer of stratification occurs between the first solvent and the second solvent; (a3) adding the carbon nanorod dispersion to the layered liquid surface between the first solvent and the second solvent; (a4) Pulling the first substrate out of the container to obtain the first substrate carrying carbon nanorods.

5. The method according to claim 4, characterized in that The concentration of the carbon nanorod dispersion in step (a1) is 1 to 3 mg / mL.

6. The method according to claim 4, characterized in that The diameter of the carbon nanorods in the carbon nanorod dispersion in step (a1) is 100 nm to 10 μm.

7. The method according to claim 4, characterized in that The length of the carbon nanorods in the carbon nanorod dispersion in step (a1) is 0.5 to 100 μm.

8. The method according to claim 4, characterized in that The solvent in the carbon nanorod dispersion in step (a1) includes any one of ethanol, methanol and isopropanol, or a combination of at least two of them.

9. The method according to claim 4, characterized in that Step (a2): the first substrate comprises a silicon wafer or a glass wafer.

10. The method according to claim 4, characterized in that Before step (a2), the method further includes soaking the first substrate in a piranha solution, and then washing and drying the substrate.

11. The method according to claim 10, characterized in that The cleaning is performed by using deionized water.

12. The method according to claim 10, characterized in that The drying is carried out by blowing with nitrogen.

13. The method according to claim 4, characterized in that In step (a2), the first solvent is water.

14. The method according to claim 13, characterized in that In step (a2), the first solvent is deionized water.

15. The method according to claim 4, characterized in that In step (a2), the second solvent is any one of n-hexane, benzene, toluene, xylene, chlorobenzene, dichlorobenzene and dichloromethane, or a combination of at least two thereof.

16. The method according to claim 4, characterized in that After step (a4), a drying process is also included.

17. The method according to claim 16, characterized in that The drying process is performed at 60-80° C. for 1-3 hours.

18. The method of claim 1, wherein: The rate of metal Ti deposition in step (a) is 19. The method according to claim 18, characterized in that The rate of metal Ti deposition in step (a) is 20. The method of claim 1, wherein: After step (a), the method further comprises subjecting the product obtained in step (a) to silanization treatment.

21. The method of claim 20, wherein: The silanization treatment comprises: dripping TMCS on the surface of the product obtained in step (a).

22. The method of claim 20, wherein: The silanization treatment time is 10 to 20 minutes.

23. The method of claim 1, wherein: Step (b) The preparation process of the second substrate includes: coating a mixed material of PDMS and sylgard 184 on the substrate, and baking to obtain the second substrate.

24. The method of claim 23, wherein: The substrate includes a silicon wafer or a glass wafer.

25. The method of claim 23, wherein: The coating method is spin coating.

26. The method of claim 25, wherein: The rotation speed of the spin coating is 500-1500 rpm.

27. The method of claim 25, wherein: The spin coating time is 30 to 90 seconds.

28. The method of claim 23, wherein: The coating thickness of the mixed material is 0.4-0.8 mm.

29. The method of claim 23, wherein: In the mixed material, the mass ratio of PDMS to sylgard 184 is (8-15):

1.

30. The method of claim 23, wherein: The baking temperature is 60-90°C.

31. The method of claim 23, wherein: The baking time is 5 to 15 minutes.

32. The method of claim 1, wherein: The process of transferring the carbon nanorods with metal Ti deposited on the upper surface to the second substrate in step (b) includes: laminating the side of the second substrate coated with the mixed material with the side of the carbon nanorods with metal Ti deposited on the upper surface, baking at 60-90° C. for 5-15 minutes, and peeling off the first substrate.

33. The method of claim 1, wherein: The thickness of the metal Ti deposited on the upper surface of the carbon nanorods in step (a) is the same as the thickness of the metal Ti deposited on the lower surface of the carbon nanorods in step (b).

34. The method of claim 1, wherein: After step (b), the method further includes the steps of peeling off the second substrate, washing with an alkaline solution, washing with deionized water and drying.

35. The method of claim 34, wherein: The alkaline solution washing is ultrasonic washing in a NaOH solution.

36. The method of claim 35, wherein: The alkaline solution washing is performed by ultrasonication in a 0.1-1 mol / L NaOH solution for 4-8 minutes.

37. The method of claim 1, wherein: The burning temperature is 300-700°C.

38. The method of claim 1, wherein: The reducing agent includes Mg powder and / or zinc powder.

39. The method of claim 1, wherein: The mass ratio of the added amount of the reducing agent to the Ti-plated carbon nanotubes is (0.5-1.5):

1.

40. The method of claim 1, wherein: The atmosphere of the reduction process is a nitrogen atmosphere.

41. The method of claim 1, wherein: The temperature of the reduction process is 600-700°C.

42. The method of claim 1, wherein: The time of the reduction process is 5 to 10 hours.

43. The method of claim 1, wherein: The pickling is performed by ultrasonication in an acid solution for 5 to 15 minutes.

44. The method of claim 43, wherein: The acid solution is any one of hydrochloric acid solution, sulfuric acid solution, phosphoric acid solution, oxalic acid solution and acetic acid solution, or a combination of at least two thereof.

45. The method of claim 44, wherein: The concentration of the hydrochloric acid solution is less than 7 wt %.

46. ​​The method of claim 44, wherein: The concentration of the sulfuric acid solution is less than 5wt%.

47. The method of claim 44, wherein: The concentration of the phosphoric acid solution is less than 85 wt %.

48. The method of claim 44, wherein: The concentration of the oxalic acid solution is less than 85 wt %.

49. The method of claim 44, wherein: The concentration of the acetic acid solution is less than 85 wt %.

50. The method of claim 1, wherein: The method comprises the following steps: (1) Pretreatment of carbon nanorods: (a) The glass and silicon wafers were immersed in piranha solution, then rinsed with deionized water and dried with nitrogen gas; (b) dispersing the carbon nanorods in an ethanol solution and ultrasonicating for 5 to 15 minutes to prepare a carbon nanorod dispersion with a concentration of 1 to 3 mg / mL; (c) Take a clean small culture dish, put a clean small glass spacer and a silicon wafer in order, and stack the silicon wafer on the small glass spacer; (d) adding deionized water until the liquid level is higher than the upper surface of the silicon wafer, and then adding n-hexane to cause stratification; (e) using a pipette to drop the carbon nanorod dispersion from the edge of the culture dish so that it spreads into a monolayer film at the layering surface of n-hexane and water; (f) Using tweezers, carefully and slowly reach under the liquid surface, pick up the silicon wafer, slowly pull out the silicon wafer, and dry it in a drying oven at 60-80° C. for 1-3 h to obtain a silicon wafer loaded with carbon nanorods; (2) Preparation of Ti-coated carbon nanorods: (g) placing the silicon wafer loaded with carbon nanorods into an electron beam evaporation system, and making the vacuum degree in the evaporation chamber reach 10 -6 ~5×10 -6 Torr, at the upper surface of the carbon nanorod at a rate Depositing metal Ti with a thickness of 10 to 100 nm; (h) adding a few drops of TMCS to the product obtained in step (g) in a culture dish, and silanizing the sample for 10 to 20 minutes; (i) Spin-coat a 0.4-0.8 mm thick mixed material of PDMS and sylgard 184 in the ratio of (8-15):1 on a clean silicon wafer, and bake at a low temperature of 60-90° C. for 5-15 min; (j) laminating the silicon wafer coated with the mixed material on the mixed material surface with the surface of the carbon nanorods in the sample obtained in step (h) on which the metal Ti is deposited, baking at 60 to 90° C. for 5 to 15 min, and peeling off the silicon wafer; (k) repeating step (g) with the sample obtained in step (j) to deposit the same thickness of metal Ti on the lower surface of the carbon nanorods; (l) peeling off the silicon wafer coated with the mixed material, ultrasonicating in a 0.1-1 mol / L NaOH solution for 4-8 min, centrifuging and filtering out the precipitate, washing with deionized water and drying; (3) Preparation of Ti nanotubes: (m) taking the sample in step (l) and burning it in oxygen at 300-700° C., and cooling it; (n) then adding Mg powder, treating at 600-700°C for 5-10 hours in nitrogen, and cooling to room temperature; (o) The sample is taken out and added into a dilute hydrochloric acid solution, ultrasonicated for 5 to 15 minutes, washed with deionized water and dried to obtain Ti nanotubes.

51. A Ti nanotube, characterized in that: The Ti nanotube is prepared by the method according to any one of claims 1 to 50, and the length of the Ti nanotube is 20 to 100 μm.

52. The Ti nanotube according to claim 51, characterized in that The side wall thickness of the Ti nanotube is 10-100 nm.

53. The Ti nanotube according to claim 51, characterized in that The inner diameter of the Ti nanotube is 100 nm to 10 μm.

54. A use of the Ti nanotube according to any one of claims 51 to 53, characterized in that: The Ti nanotubes are used in the field of life sciences.

55. The use of Ti nanotubes as claimed in claim 54, characterized in that: The Ti nanotubes are used in any one of biotechnology injection equipment, biosensors, nanocapsules, stents, tissue engineering and drug delivery, or a combination of at least two thereof.

Citation Information

Patent Citations

  • Ti nanotube

    CN213112520U

  • One-dimensional titanium nanostructure and method for fabricating the same

    US20140193289A1